2022
DOI: 10.1186/s12889-022-13851-0
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable predictors of health literacy in working-age adults - a rapid review and meta-analysis

Abstract: Background Health literacy comprises the ability to identify, obtain, interpret and act upon health information. Low health literacy is a major risk factor for hospitalizations, use of emergency care and premature mortality among others. Known risk factors for low health literacy such as lower educational attainment, migration history and chronic illnesses overlap with those for long-term unemployment – in itself a risk factor for low health literacy. These factors are difficult to address in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
0
12
0
3
Order By: Relevance
“…Several sociodemographic factors that were described as associated with HL in previous studies were assessed herein [ 6 , 7 , 12 , 14 , 24 – 27 ]. It has been shown that the elderly, individuals with disabilities, those with lower socioeconomic status, ethnic minorities, and those with limited education had a lower HL level [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several sociodemographic factors that were described as associated with HL in previous studies were assessed herein [ 6 , 7 , 12 , 14 , 24 – 27 ]. It has been shown that the elderly, individuals with disabilities, those with lower socioeconomic status, ethnic minorities, and those with limited education had a lower HL level [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic variables collected were: age (categorized from 18-25 to >75 in 10-year intervals as used in the study reporting the development and validation of the HLS 19 -Q12 study [ 15 ]), sex (male or female), country of birth, native language), level of education (less than middle school, middle school, high school, more than high school), profession, perceived health status (very good, good, bad, very bad), internet access (yes or no), living environment (rural or urban), isolated (yes or no). These sociodemographic factors were chosen because they had already been reported to be associated with HL [ 6 , 7 , 12 , 14 , 24 – 27 ]. We added whether they were referred to the ED by a physician (either during a consultation or by telephone, including via the emergency telephone number for medical help; yes or no) could potentially been linked with HL level.…”
Section: Methodsmentioning
confidence: 99%
“…Aus den WHO/EU-Datenauswertungen von 2021 wurden aus den einzelnen Health-Literacy-Kategorien jene Aufgaben selektiert, die als am schwierigsten zu bewältigen beschrieben wurden [12] [13].…”
Section: Am Schwierigsten Zu Bewältigende Aufgabenunclassified
“…Dafür sind Vorinformationen notwendig, um aus der Fülle an Auswahlmöglichkeiten seriöses Material selektieren zu können. Auch das ist schwierig, wenn die Landessprache nicht gut beherrscht wird [13].…”
Section: Am Schwierigsten Zu Bewältigende Aufgabenunclassified
“…Studies of health literacy have revealed low rates: 36% in the United States (Kutner et al, 2006), 47.6% in the European Union (Sørensen et al, 2015), and 64.6% in Turkey (Durusu Tanrıöver et al, 2014). Research reports a significant relationship between health literacy level and older age, socioeconomic level, and education (Beauchamp et al, 2015; Schillinger, 2020; Singh et al, 2022; Yuen et al, 2018).…”
mentioning
confidence: 99%